Consistency between the distributions for the two phases in aeolian sand transport: Impact of sand on wind - Bin Yang; Yuxin Liu; Jianjun Qu (AIP Advances)
A field observation was conducted to collect the gust signal at different heights above the bed surface, and the normalized probability distribution function of gust strength was obtained. The result shows that below the height of 800 mm, the closer to the bed, the greater the rise in the left half of the distribution map, indicating that the reduction in gust strength mainly occurs in the low velocity range. The distribution of particle size at bed surface and the normalized gust strength belong to the same distribution. Specifically, the particle size distribution is quantitatively in accordance with the gust distribution at the height of 300 mm, which denotes the thickness of the saltation layer. In accordance with the two characteristic heights (300 and 800 mm), the region near bed surface is divided into three parts, namely, the active zone (within 300 mm), the subactive zone (300–800 mm), and the inert zone (above 800 mm). Accordingly, a point-to-point equivalent momentum exchange theory between the wind and the sand is proposed, which is convenient for predicting the local wind conditions with the information of sand particle size.